Penggunaan model project based learning untuk meningkatkan meningkatkan kemampuan berpikir kreatif kolase untuk siswa kelas II sekolah dasar - Cucu Mulyati; Siti Ruqoyyah; Medita Ayu Wulandari (COLLASE (Creative of Learning Students Elementary Education), 2024)
This research aims to find out: (1) Increasing the ability to think creatively in collage in class II elementary school students using the Project Based Learning model (2) Difficulties of class II elementary school students in improving their ability to think creatively in collage (3) Difficulty for teachers in using the model Project Based Learning in class II elementary school students. The research method used is a mix method with an Explanatory Sequential Design model. The research subjects were 30 grade II elementary school students. Data was obtained from observation sheets, response questionnaires and interviews. The quantitative data collection technique is by providing pretest and posttest questions, while for qualitative data it is by providing observation sheets, response questionnaires and interviews. From the results of the research that has been carried out, it can be concluded that the use of the Project Based Learning model to improve creative collage thinking skills in second grade elementary school students has increased. This is proven by the average n-gain score obtained at 0.58 with medium criteria, which means the effectiveness is moderate. The students' difficulties in this research were that students had difficulty in developing collage artwork in elaboration, lack of interest in SBdP learning, students had difficulty in concluding the material. The difficulties faced by teachers in this research were limited tools and materials, lack of learning time, and difficulties for teachers to condition students